Co-existing study of a radar and communication (Radcomm) system - Tan, Danial Norman Jee Chuan (Nanyang Technological University, 2021)
In this report, we study the coexistence of a communication system and a radar system. Binary phase shift keying (BPSK) digital modulation technique in a complex envelope form is considered for the communication system while a frequency modulated continuous waveform (FMCW) is considered for the radar system. MATLAB programming was used to design the coexisting system and conduct test simulations to evaluate the performance of the system. Interference cancellation was then applied to the coexisting signal to remove the interfering signal in the coexisting system. The performance evaluation for the communication aspect of the coexisting system will be based on the bit-error rate (BER) while the detected target range will determine the performance of the radar system using range-speed response pattern (RSRP) plots.